Analysis of Food Intake and Nutritional Status Among Pregnant Women in Rural Areas - Nurhayati Nurhayati; Rani Suraya; Romiza Arika; Putra Apriadi Siregar (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Pregnancy is an important period for a mother to fulfil nutritional needs for herself and for the growth and development of the fetus because fetal nutrition depends on maternal nutrition, so the mother's nutritional needs must also be met. Inadequate energy and protein intake in pregnant women can cause Chronic Energy Deficiency (CED). This research aims to determine the food intake of pregnant women in Bagan Serdang Village Deli Serdang District. The sample was determined by purposive sampling, where pregnant women who became respondents were pregnant women with criteria experienced food insecurity, namely 20 people. Data on food intake was obtained using the 24-hour recall method and personal data through interviews with pregnant women. Data were analyzed by nutrisurvey tools to determine the amount of food intake. Chronic Energy Deficiency (CED) data was measured using an upper arm circumference tape. Data analysis was done descriptively to describe the food intake of pregnant women, including energy, carbohydrate, and protein intake. The results showed that 15% of pregnant women experienced Chronic Energy Deficiency (CED), and 60% of pregnant women's energy intake was still lacking. Intake of carbohydrates and protein still falls short of the nutritional requirements for pregnant women, with 55% and 75% falling into the deficient category, respectively. For pregnant women to avoid Chronic Energy Deficiency (CED), the public health center and cadres must increase their understanding of the importance of balanced nutrition during pregnancy. Keyword: Consumption, Food intake, Food, Pregnant women